Partai Islam dalam Dinamika Demokrasi di Indonesia - Yumitro, Gonda (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
Some surveys showed that though Islamic parties had significant supports in 1999 and 2004 elections and their existences are in the largest Muslim population in the world, the current development indicates the decline supports of people on them. This paper will analyze various factors which cause such phenomena and predict the Islamic parties position on 2014 election. The result found that Islamic parties will face tough position on next election because of democracy, Indonesian Islamic characteristics and history, the competence of Islamic parties, and other external factors. The democracy causes a lot of problems, like the conflict among Islamic groups in Indonesia, which had dark history as the consequence of the politization of Islam by the elites. Moreover, the involvement of Islamic parties in Indonesian politics has not able to solve the real problems within the society, such as poverty, unemployment, corruption, etc. Unfortunately, the public opinion and education characters in Indonesia also donât support the Islamic political parties position.